ANALISIS PELAKSANAAN LITERASI DIGITAL DALAM PROSES PEMBELAJARAN SOSIOLOGI DI KELAS XI IIS MAN 1 PONTIANAK - Devi, Devi; Sulistyarini, Sulistyarini; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to determine the implementation in the learning process of sociology in class XI IIS MAN 1 Pontianak using digital literacy. The research approach used is qualitative research with descriptive approach method. Data collection techniques used were observation, interview and documentation study. This research was presented in a qualitative descriptive manner using 6 informants. Sociology learning using digital literacy has a variety of processes, namely, accessing, assembling, understanding, and disseminating information. When starting learning the teacher gives a web address to students of class XI IIS, the web address will be accessed by students using their own personal cellphones, after accessing students directed to compose readings from what they have obtained from the web address / link given by the teacher sociology, after assembling students is given time to understand so that when the teacher has directed students to come to the front of the class, students have been able to disseminate information in accordance with what they have gotten from digital media. Even though it has gone very well, there are various kinds of obstacles experienced by teachers and students, namely the lack of digitalbased learning media. Keywords:, Access, Assemble, Digital Literacy, Disseminate information, Understand